Abstract # 3189 Weighted gene co-expression network analysis suggests interferon activity is associated with depression severity - Toups, M.; Arasappan, D. (Brain, behavior, and immunity, 2019)
To further the identification and treatment of patients with mood disorders having an immune component, we must identify the specific nature of immune processes associated with mood. We analyzed peripheral blood RNA sequencing data from the Depression Genes and Networks (DGN) Study using Weighted Gene Co-expression Network Analysis (WGCNA) from 441 adult subjects with a past or current diagnosis of Major Depressive Disorder. After filtering, 5778 genes were clustered in 19 modules. Overall, modules had weak clinical correlation; one module containing 63 genes showed the best correlation with scores on the 9-item Public–Health Questionnaire (PHQ-9) (r = 0.1, p = 0.03). This module was significantly enriched for the Gene Ontology Biological Process Type I Interferon Signaling (adjusted p? 0.001) and other pathways of anti-viral immunity. This module significantly overlapped with a module of 74 genes derived from 325 subjects from the DGN healthy control sample; it did not correlate significantly with any clinical trait in those subjects. One module of 52 genes from the depressed sample, containing primarily immunoglobulin chain genes, had no corresponding module in the healthy sample. This module, however, did not correlate significantly with any clinical trait. These findings replicate the previously published association of Interferon pathways with depression in this sample. Replication in an independent sample is necessary to validate the role of antiviral immunity in depression.